The Centre for Multilingualism and Diversities Research at the University of the Western Cape, South Africa - Stroud, Christopher (Multilingual Margins: A journal of multilingualism from the periphery, 2023)
There is an urgency in theorising how diversity is negotiated, communicated, and disputed as a matter of everyday ordinariness that is compounded by the clear linkages between diversity, transformation, voice, agency, poverty and health. The way in which difference is categorised, somatised and reconfigured in multiple languages across quotidian encounters and in public and media forums is a central dynamic in how poverty and disadvantage are distributed and reproduced across social and racial categorisations. In the South African context, finding ways of productively harnessing diversity in the building of a better society must be a priority.